Building Effective Employment Programs for Unemployed Youth in the Middle East and North Africa - Angel-Urdinola, DiegoF. (World Bank, 2015)
Given the labor market challenges that countries in the Middle East and North Africa (MENA) region are facing (notably high unemployment, prevalence of skills mismatches, low labor market mobility, and lack of formal employment networks), employment services could be a relevant policy instrument to assist unemployed individuals to find jobs. Despite high and increasing unemployment rates, employers in the region are facing difficulties to find workers whose competences and skills fit their employment needs.